Parametric study on the effects of pinch and approach points on heat recovery steam generator performance at a district cooling system - Nordin, A. (Universiti Malaysia Pahang, 2016)
Heat recovery steam generators are important equipment at district cooling plants. The capability of heat recovery steam generators in generating steam influences the steam absorption chiller's performance. The steam generation capability of the heat recovery steam generators in turn is linked to the values of pinch point and approach point. Hence, a study on the pinch point and approach point for the heat recovery steam generators would be useful in understanding the effects of varying pinch point and approach point values to the heat recovery steam generators' performance. In relation to this subject, a parametric study on the heat recovery steam generators was done. The study covered the effects of the pinch point and approach point on the following: mass flow rate of steam generated; exhaust heat temperature leaving the heat recovery steam generators; and the efficiencies of the heat recovery steam generators. The first law of thermodynamics was used for the analysis. Four scenarios were covered in the study: the effects of the pinch point and approach point on steam generation; the effects of the pinch point and approach point on the exhaust heat temperature leaving the heat recovery steam generators; the effects of the pinch point and approach point on the efficiency of the heat recovery steam generators; and the effects of the exhaust heat temperature of the gas turbine on the mass flow rate of steam. Operating data at Universiti Teknologi PETRONAS gas district cooling plant were used to validate the model. The results from the first scenario indicated that higher pinch point and approach point led to a decrease in the steam being generated. For the second scenario, the increase in pinch point and approach point resulted in higher exhaust heat temperature leaving the heat recovery steam generators. Meanwhile, for the third scenario, it was noted that there was only a minimal variation of the efficiency of the heat recovery steam generator when the pinch point and approach point were increased. The findings of the fourth scenario indicated that with higher gas turbine exhaust heat temperatures, there was an increase in steam being generated. Therefore, the findings could be useful for the plant to set the operating parameters for operating heat recovery steam generators. Â© Universiti Malaysia Pahang.